Authenticity, Satisfaction, and Place Attachment: A Conceptual Framework for cultural tourism in African Island Economies - Ramkissoon, Haywantee (Routledge, 2015)
Small islands often host distinctive resources to influence their future through tourism development. Island economies in Africa have witnessed a growing number of tourists seeking authentic cultural and natural heritage tourism attractions. This paper critically examines and bridges the nexus between perceived authenticity, place attachment, place satisfaction and cultural behavioural intentions of tourists in African island economies. Adopting a theoretical framework from the authenticity literature, and the attitude-behaviour framework, this paper develops and proposes a conceptual model to investigate how authenticity of a cultural tourism attraction might influence place satisfaction, which in turn might influence levels of place attachment and prompt cultural behavioural intentions of tourists in African island economies. This research conceptually contributes to knowledge advocating the associations between constructs of authenticity, place satisfaction, place attachment, and cultural behavioural intentions of tourists in African island economies. Limitations of the study and practical implications for sustainable tourism development are discussed.